Power, motivation and females aggression, a qualitative study - Edalati, Ali; Redzuan, Ma'rof (Medwell Journals, 2010)
This study examines qualitatively the motivation of women about power and effect on female’s aggression. The research studied ten women, who were already registered in counselling clinics, whom suffered from aggression (physical and psychological). The results revealed that the females have pointed out they do not want to have dominance on their husbands but they were looking for equality in their relationship. Female aggression was a part of the partners attempt for power.